2005
DOI: 10.1007/s11664-005-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Detailed study of above bandgap optical absorption in HgCdTe

Abstract: HgCdTe remains the material of choice for high-performance infrared (IR) detectors due to its tunable direct bandgap energy corresponding to the IR spectral region, and the advancement of HgCdTe materials growth and processing technologies. Accurate knowledge of the HgCdTe optical absorption coefficient is important for IR detector design, layer screening, and device analysis. The spectral response for IR detectors is dependent on optical absorption above the bandgap energy, where much of the study of absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…In our current simulations we use the Hougen 15 model, which provides the results shown. We are aware of recent suggested improvements 16,17 and we will test them in future developments of this work. Below 11 lm the discrepancy increases; in particular the measured external data falls lower than the simulated external data, but this is mainly a measurement artifact of the experimental set-up.…”
Section: Single-pixel Resultsmentioning
confidence: 99%
“…In our current simulations we use the Hougen 15 model, which provides the results shown. We are aware of recent suggested improvements 16,17 and we will test them in future developments of this work. Below 11 lm the discrepancy increases; in particular the measured external data falls lower than the simulated external data, but this is mainly a measurement artifact of the experimental set-up.…”
Section: Single-pixel Resultsmentioning
confidence: 99%
“…The formula for a used by Pellegrino and DeWames 16 when fitting measured quantum efficiency for the T2SL gives 1620 cm À1 at 9.813 lm. In comparison, the formula for Hg 1Àx Cd x Te by Moazzami et al 17 (with x = 0.2194) gives 2017 cm À1 at 9.813 lm. Thus, in this example, the absorption coefficient at a wavelength 1 lm shorter than the cutoff is smaller in the T2SL than HgCdTe by only about 20%.…”
Section: Significance Of Dark Currentsmentioning
confidence: 86%
“…(6) by assuming the dispersion relationships E c ðkÞ ¼ k 3 1þc þ E g and E lh ðkÞ ¼ Àk 2, corresponding to 0.5 £ c £ 2, exactly the same range as in our previous discussions. Moazzami et al 27 have empirically determined a c value of approximately 0.7 for a Hg 0.69 Cd 0.31 Te sample in the energy range of about 100 meV above the energy gap. Chu and co-workers 18,28 found that a logarithmic approximation works best in the energy range of 100 meV above the energy gap.…”
Section: Resultsmentioning
confidence: 99%